Effects of seeds ingestion by Lagune cattle and other pre-planting treatments on the germinability of Centrosema pubescens Benth seeds in Soudanian region of Benin (West Africa) - Houndjo, Daniel; ADJOLOHOUN, SÉBASTIEN; ADENILE, DOUROSSIMI ADAM; GBENOU, Basile; SAIDOU, ALIOU; AHOTON, Léonard (My University, 2019)
In Benin under extensive management of grassland, there is little information about legumes regeneration and management in pastures. This trial evaluated the germination of Centrosema pubescens seeds after passage through the digestive tract of three young bulls and three heifers of Lagune breed cattle. Following seeds ingestion by cattle, total faeces were collected at 24-h intervals for 6 days after which time the faeces were sieved and the surviving intact seeds were then collected, counted and germination tests undertaken. Moreover, the effect of soaking seeds with hot water and mechanical scarification on breaking of dormancy in seeds of C. pubescens were studied through seven treatments: control (1); scarification using sandpaper (2); and seeds were immersed in hot water (80°C) for 2 (3), 4 (4), 6 (5), 8 (6), and 10 min (7). The total number of seeds recovered represented 7.65% of the number fed. The number of seeds recovered after 72 h represented more than 91.00% of total seeds recovery. Overall germination percentage of seeds recovered (45.09%) was greater than that of untreated seeds (31.00%). Seedling emergence was significantly higher when dung was broken-down than when left intact. Generally, it was observed that mechanical scarification was the method that had the highest percentage of germination (96.00%), followed by seeds immersed in hot water at 80°C for 2 to 4 min and seeds ingested by cattle. Therefore, endozoochory and other pre-planting seeds treatments can potentially favour seed germination of C. pubescens and contribute to the improvement of degraded grassland.
Keywords: Centrosema pubescens; sandpapering; endozoochorous; hot water; germination; Benin.